Commentary: unions and the evolution of trade and industry policy under the ardern government. (3rd July 2021) - Rosenberg, Bill
ABSTRACT: New Zealand's structural development has been dominated for the last generation by a strongly neoliberal, market-focused orientation. The country has signed several neoliberal free trade agreements, and for long periods largely abandoned active or strategic industry policy. It has seen the steady decline of manufacturing as a proportion of total production and of higher value manufacturing as a proportion of exports, and failed to significantly diversify its exports, retaining high dependence on a few primary commodity exports. Productivity performance has been notably poor. The Labour-led government elected in 2017 has demonstrated its willingness to at least partly break with neoliberal precepts in other policy areas; this commentary surveys its approach to date in industrial and trade policy reforms, and the role of unions in these developments. There are initial promising steps but the free trade agreements place significant restraints on what is possible.